The development of corporate security in the context of countering threats to doing business - Taras Shyra; Kostiantyn Salyga; Vasyl Derii; Igor Prykhodko; Svitlana Shymkiv (Business: Theory and Practice, 2021)
The principal purpose of the study is to determine the main parameters of corporate security development in the enterprise in the context of determining the level of impact of external and internal threats. The study uses survey methods on the main internal and external threats that may affect the corporate security of enterprises. The purpose of the practical part of our study is to determine the level of these threats to corporate security. The methodological basis of our study is the method of expert evaluation, which was conducted by interviewing people involved in the process of corporate security management of enterprises, as well as methods of the hierarchical organization using matrices of pair-wise comparisons. The major results of the study can be considered determining the hierarchy of influence of each of the threats affecting the corporate security of industrial enterprises, which will allow optimizing the security system and directing its activities to more pressing issues. Our method of the hierarchical organization of threats to corporate security does not take into account the specifics of the corporate security system of industrial enterprises in most European countries and now can be freely implemented mainly in industrial enterprises of Eastern Europe. The proposed method of assessing external and internal threats is currently optimized for the activities of industrial enterprises in Eastern Europe, including Ukraine and Poland. In the following, at an expansion of the given research, there is a possibility of introducting this methodology to the enterprises of other countries or other profiles. The relevance of this study lies in determining the level of threats that affect the corporate security of industrial enterprises. The methodology for assessing the level of influence of these threats is universal, therefore it can be used in the event of a change in the main threats, it is extremely relevant in the context of rapid globalization changes in the world.
Keywords: M14; G34; P42; L21; 650; corporate security; parameters of the development; external and internal threats; risk; enterprise; matrix; the relationship graph